Objective evaluation of facial features in Congolese newborns by facial measurements. The need for population‐specific measurements. Issue 10 (20th August 2022) - Mubungu, Gerrye; Roelants, Mathieu; Lumaka, Aimé; Makay, Prince; Tshika, Dahlie; Lubala, Toni; Tshilobo Lukusa, Prosper; Devriendt, Koenraad
Abstract: The evaluation of dysmorphism is often subjective because many continuous traits are not easily measured or lack normal values. Because many common morphologic profiles vary between populations, population‐specific reference ranges of relevant traits are needed. We aim to evaluate the objective assessment of facial dysmorphism in 553 Congolese newborns based on facial measurements. Measurements taken with a ruler were on average larger compared to those with a caliper, but the bias did not depend on the size of the measurement. We therefore introduced a correction factor that allows to use both techniques for facial measurements interchangeably in future studies. The outer canthal distance, palpebral fissure length, and mouth width were significantly larger in Congolese newborns (respectively mean 6.59 [ SD 0.48]; mean 2.20 [ SD 0.24]; mean 2.78 [ SD 0.26]) when compared to references based on European newborns (respectively mean 3.59 [ SD 1.76]; mean 4.20 [ SD 2.26]; mean 0.47 [ SD 1.21]), while the rest of measurements were significantly smaller. The interpupillary distance (IPD) calculated from inner canthal distance and outer canthal distance was not significantly different. We observed a poor agreement between clinical evaluation and measured features (kappa of 0.432). Clinicians were more likely to recognize a face as having wide‐spaced eyes when it had been recognized as such during the clinical examination, more than if the child had a high interpupillary distance. This suggests that the measured IPD is not precisely reflecting what is clinically evaluated as wide‐spaced eyes.